Implementasi Smart Economy Dalam Pemberdayaan Industri Kecil Menengah Kota Kediri Menuju Smart City - Caisar Pieter Vega Arwanto; Sri Wibawani (PERSPEKTIF, 2022)
This research was conducted by the author entitled "Implementation of Smart Economy in Empowering Small and Medium Industries of Kediri City Towards Smart City". The purpose of this study is to analyze how the implementation of a smart city in empowering small and medium industries in the city of Kediri towards a smart city. This is done because the City of Kediri has potential in the industrial sector, as well as many other potentials such as tourism, and typical Kediri products such as tofu and woven fabrics. The author uses a policy implementation model that can affect the success of implementation according to Van Metter and Van Horn. The type of research used is descriptive research with a qualitative approach. The results of this study, the government of the City of Kediri has implemented the smart economy in empowering small and medium industries, it is well seen that there are many business actors who are on-boarding in digital marketing, and there are many programs, trainings, and workshops conducted by the government of the City of Kediri to the public. businessmen. This study concludes that the implementation of the smart economy in empowering small and medium industries has been going well, but there are still obstacles, one of which is the limited budget, because the focus of the budget is on health issues.